Analisis Relationship Marketing dan Kualitas Pelayanan Terhadap Loyalitas Nasabah Bank BTN melalui Corporate Social Responsibility Sebagai Variabel Intervening - Musfiroh Indah Sari; Versiandika Yuda Pratama (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2023)
This study aims to examine the impact of relationship marketing and service quality on customer loyalty at Bank Tabungan Negara (BTN), with corporate social responsibility as a moderating factor. This research is a type of quantitative research. The data collection method in this study used a questionnaire with a total sample size of 100 respondents. The sample was selected using the accidental sampling method. The data analysis technique in this study used path analysis with the Sobel test. The results showed that all variables had a partial positive relationship with loyalty. This study found that while corporate social responsibility can mediate relationship marketing to BTN customer loyalty, it cannot mediate service quality to BTN customer loyalty.